1994
DOI: 10.1016/0168-9002(94)90691-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of microstrip gas chamber design and operating conditions

Abstract: the width of the cathode strips from 80 ttm to 160 ttm.anodes we predict an increase by a factor of 4 of the maximum gain when increasing gains before discharges can be obtained for wide cathodes: as an example, for 10 pm estimated the optimum geometry of the detectors. The results indicate that higher that computes fields and gains and applying the discharge criterion, we have combined field strength at the edges of the anode and cathode strips; using a programWe also discuss a model to characterize the break… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 6 publications
2
19
0
Order By: Relevance
“…Large ion current towards the drift electrode at high drift fields is typical for MSGCs. The charge gain of the MSGC is also sensitive to the strength of drift field for given voltage on the cathodes [10]. Result presented in figure 6 shows that at drift fields above 400 V/mm the charge gain increases.…”
Section: Effect Of Drift Fieldmentioning
confidence: 75%
“…Large ion current towards the drift electrode at high drift fields is typical for MSGCs. The charge gain of the MSGC is also sensitive to the strength of drift field for given voltage on the cathodes [10]. Result presented in figure 6 shows that at drift fields above 400 V/mm the charge gain increases.…”
Section: Effect Of Drift Fieldmentioning
confidence: 75%
“…Unfortunately, substrate effects have led to considerable difficulties with operational stability, particularly at high flux levels . Various studies to determine the optimum configuration for an MSGC have been performed (Bouclier, Garabatos, Manzin, Sauli, Shekhtman & Temmel, 1993;Beckers, Bouclier, Garabatos, Million, Sauli & Shekhtman, 1994 1993; Allunni, Bouclier, Fara, Garabatos, Manzin, Million, Ropelewski, Sauli, Shekhtman, Daubie, Pingot, Pestov, Busso & Costa, 1993;Budtz-Jorgensen, Bahnsen, Olesen, Madsen, Jonasson, Schnopper & Oed, 1991), but at the time of writing the optimum characteristics for an MSGC are still unclear with somewhat conflicting results being reported by different groups. It seems clear that the substrate must possess sufficient conductivity to prevent charge up and polarization, or gain instabilities will result; however, highconductivity substrates can allow high current flow which causes heating.…”
Section: Detector Designsmentioning
confidence: 99%
“…The presence of a high field on cathode edges limits the maximum voltage that can be reached in MSGCs, even in absence of radiation, due to spontaneous field emission [13]. It has been observed that under high irradiation rate and/or exposure to heavily ionizing tracks, occasional transitions from proportional avalanche to streamer occur at high operating voltage, most of the times followed by a discharge, harmful and often fatal to the delicate structures and readout electronics.…”
Section: Introductionmentioning
confidence: 99%